The Effectiveness of Project-Based Learning Model in Increasing Understanding of Mathematical Concepts in Fourth-Grade Elementary School Students - Sevani, Olivia; Ramadan , Zaka Hadikusuma (LPPM Undiksha, 2023)
Learners are less able to optimize the project-based learning model. Many students still have not been trained to think critically and creatively toward understanding mathematical concepts, and children are less able to cooperate. This study aimed to analyze the effectiveness of the Project Based Learning model. This research used quantitative methods with the type of pre-experiment and a one-group pretest-postest design. The population in this study was taken from class IV, which consisted of 3 classes. The research sample consisted of class IVC, as many as 33 people. Research data were collected through the test method. The data analysis technique in the study used descriptive analysis and prerequisite tests using SPSS release 24 for Windows, r_hitung more than 0.361, so the 10 test items were declared valid and suitable for researchers to use. Based on the alpha stability category, a score of 0.658 is included in the reliable category, so it can be concluded that the test questions submitted are reliable. In the Paired Sample, t-test results with a significant score of 0.000 less than 0.05 show a significant difference in applying the project-based learning model in improving the understanding of mathematical concepts of fourth-grade elementary school students. So, it can be concluded that the treatment of post-test results by applying the project-based learning model effectively improves the understanding of mathematical concepts of grade IV elementary school students.